ФОРМИРОВАНИЕ ТЕРРИТОРИАЛЬНЫХ МИНЕРАЛЬНО - СЫРЬЕВЫХ КОМПЛЕКСОВ В РЕСПУБЛИКЕ КАРАКАЛПАКСТАН - Ешимбетов, У.Х.; Искендеров, А.Б.; Турдыбекова, З.М.; Атамуратов, И.А. (SCIENCE and SOCIETY, 2022)
The article describes the priority areas of industrial development of areas that do not have mineral resources. It was noted that it is necessary to transform such regional centers as Takhtakupyr, Shumanay, Bozatau, Karauzyak, Kegeili, Kanlykul, Muynak and Akmangit into points of growth.
Keywords: economy; mineral resources; chemical industry; district; territory